A REVIEW ON DYNAMIC RESOURCE ALLOCATION BASED ON LEASE TYPES IN CLOUD ENVIRONMENT (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
Load balancing is one of the essential factors to enhance the working performance of the cloud service provider. Cloud Computing is an emerging computing paradigm. It aims to share data, calculations, and service transparently over a scalable network of nodes. Since Cloud computing stores the data and disseminated resources in the open environment. Since, cloud has inherited characteristic of distributed computing and virtualization there is a possibility of machines getting unused. Hence, in this paper, different load balancing algorithms has been studied. Different kinds of job types have been discussed and their problems have been reviewed. In the cloud storage, load balancing is a key issue. It would consume a lot of cost to maintain load information, since the system is too huge to timely disperse load. Load balancing is one of the main challenges in cloud computing which is required to distribute the dynamic workload across multiple nodes to ensure that no single node is overwhelmed.